Barwna postać w sutannie. Ksiądz Wiktor Krąkowski (1827–1880), administrator parafii Borszewice, cz. I: okres wikariatu (do 1853 r.) - Szkutnik, Piotr (Biuletyn Szadkowski, 2008)
The study of Father Wiktor Krąkowski’s life (1827–1880) has been divided into two parts due to space constrains. This is the first part presenting his young years, including the time he spent in school, mainly in the seminary in Włocławek, and his church career up to 1853. It includes information about his ancestors and closest relatives and attempts to explain the etymology of his name. Source material for the article consists mostly of church court records, hence much attention is devoted to disputes between young curate Krąkowski and his superiors – vicars of the successive parishes where he was designated. The conflicts arose as a result of his efforts to secure satisfactory livelihood for his mother and siblings.